Sintering Temperature Effect to the Synthesis of SiC Produced from Rice Husk ash and 2B Graphite Pencils - Resky Irfanita; Asnaeni Ansar; Ayu Hardianti Pratiwi; Jasruddin J; Subaer S (Department of Physics, Sebelas Maret University, 2015)
The objective of this study is to investigate the effect of sintering temperature on the synthesis of SiC produced from rice husk ash (RHA) and 2B graphite pencils. The SiC was synthesized by using solid state reaction method sintered at temperatures of 750°C, 1000°C and 1200°C for 26 hours, 11.5 hours and 11.5 hours, respectively. The quantity and crystallinity level of SiC phase were measured by means of Rigaku MiniFlexII X-Ray Diffraction (XRD). The microstructure of SiC was examined by using Tescan Vega3SB Scanning Electron Microscopy (SEM). The XRD results showed that the concentration (wt%) of SiC phase increases with the increasing of sintering temperature. SEM results showed that the crystallinity level of SiC crystal is improving as the sintering temperature increases